(untitled) (Szociológiai Szemle, 2024)
The subject is the diminishing of the work-paradigm as the basis of the industrial society and as the „model of normality" and its influence on the interpretation of leisure. Up to this time interpretation of leisure have been closely connected with interpretations of work throughout the ’modern’ and ’modernity’ periods. Those changes in the work-paradigm which might be brought over the postmodern era will radically modify the basis of leisure theories, since these changes will put these theories into novel perspectives. In everyday life, as well as in theoretical inquiries, the leisure problem tends to appear in contexts not connected to work.